Indexing quality and effectiveness: An exploratory analysis of electronic theses and dissertations representation. Issue 1 (27th December 2016) - Alemneh, Daniel; Phillips, Mark
ABSTRACT: Theses and dissertations (ETDs) represent a wealth of scholarly and artistic content created by graduate students in masters and doctoral programs in the degree‐seeking process. Considering the multi‐disciplinarity and interdiciplinarity characteristics of ETDs, often several subjects and indexing terms need to be supplied to adequately represent ETDs for efficient access. This study analyzes the quality and effectiveness of indexing terms – both authorized terms from controlled vocabularies and free‐text keywords – used to succinctly describe the content of the electronic theses and dissertations (ETDs). Based on the comparisons of the search terms entered by users to discover and access the ETDs, the authors also discuss the subjectivity and objectivity of the process and the need to distinguish functional representation from mere descriptions of a topic.